ACCESSORIES OF FISCAL OBLIGATION. LEGAL REGIME - RADA POSTOLACHE (Challenges of the Knowledge Society)
The interest – which is an institution typical to private law, has been taken over by the fiscal field and adapted to the specific features of fiscal obligation – being defined by its imperative legal regime, which has at the least the following characteristic elements: unitary character, imposed legal percentage, compulsory demand of interest, automatic application. In order to render responsible fiscal debtors, the lawmaker has reintroduced, as an accessory of fiscal obligation, delayed payment penalties, which have a distinct nature and legal regime, but without the principle non bis in idem being transgressed. Our study aims to establish the legal regime ofaccessories typical to fiscal obligation, from the perspective of special normative acts, but also of the common law within the field – Civil Code and Government Ordinance No. 13/2011 – by pointing out at the same time both the particular circumstances and procedural ones regulated by the Fiscal Procedure Code, shedding light upon the controversial legal nature of accessories.